1991
DOI: 10.1210/jcem-72-4-945
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Diiodotyrosine (DIT) in Severe Infections and Sepsis: DIT, a Possible New Marker of Leukocyte Activity*

Abstract: Ether link cleavage (ELC) of T4 yielding diiodotyrosine (DIT) has recently been shown in vitro to be the major pathway of T4 metabolism in phagocytosing leukocytes. To evaluate this pathway in vivo and the possible clinical relevance of DIT measurements in diseases with increased leukocyte activity, radioimmunological studies on serum levels of DIT and other thyroid parameters were performed in 125 critically ill patients classified into 3 groups with bacterial infections according to the severity of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The role of ECL in TH metabolism under physiological conditions is thought to be limited, since only 5% of total body clearance of TH is mediated via ELC (Faber et al 1989). However, it has been suggested that the serum concentration of DIT, a product of ELC, increase after surgery and during sepsis (Gramm et al 1989, Meinhold et al 1991, indicating that in specific pathophysiological conditions, ECL might attribute to TH clearance.…”
Section: D3 Hif1αmentioning
confidence: 99%
“…The role of ECL in TH metabolism under physiological conditions is thought to be limited, since only 5% of total body clearance of TH is mediated via ELC (Faber et al 1989). However, it has been suggested that the serum concentration of DIT, a product of ELC, increase after surgery and during sepsis (Gramm et al 1989, Meinhold et al 1991, indicating that in specific pathophysiological conditions, ECL might attribute to TH clearance.…”
Section: D3 Hif1αmentioning
confidence: 99%
“…44 Iodine in the thyroid hormones is also thought to be associated with the MPO-H 2 O 2 -halide system, and the serum DIT levels increased in patients with a severe infection because of the use of iodine in the phagocytic system. The levels of the thyroid hormones were found to increase in the serum of patients with sepsis as compared to other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There was no such localized T 4 uptake in patients who had received antibiotics for more than a week or did not have clinical signs of bacterial infection. Furthermore, Meinhold et al (43) have shown that T 4 is degraded to diiodotyrosine (DIT) in phagocytosing and therefore activated leukocytes in patients with severe infections or sepsis. DIT and its metabolites are bactericidal (44).…”
Section: Discussionmentioning
confidence: 99%